Epidermal growth factor stimulates exosomal microRNA‐21 derived from mesenchymal stem cells to ameliorate aGVHD by modulating regulatory T cells. Issue 6 (21st April 2020) - Zhu, Haojie; Lan, Lingqiong; Zhang, Yuxin; Chen, Qiuru; Zeng, Yanling; Luo, Xiaofeng; Ren, Jinhua; Chen, Shaozhen; Xiao, Min; Lin, Kangni; Chen, Minmin; Li, Qian; et al.
Abstract: Regulatory T cells (Tregs), a subset of CD4 + T cells, may exert inhibitory effects on alloimmune responses including acute graft‐versus‐host disease (aGVHD), and several microRNAs are implicated in the pathophysiological process of GVHD. Therefore, we aimed in the present study to characterize the functional relevance of epidermal growth factor (EGF)‐stimulated microRNA‐21 (miR‐21) in regulating bone marrow‐derived mesenchymal stem cells (BMSCs) in a mouse model of aGVHD. We first isolated and cultured BMSCs and Tregs. Then, we examined effects of miR‐21 knockdown or overexpression and EGF on cell activities of BMSCs and the expression of PTEN, Foxp3, AKT phosphorylation, and extent of c‐jun phosphorylation by gain‐ and loss‐of‐function approaches. The results showed that miR‐21 promoted the proliferation, invasion, and migration of BMSCs. Furthermore, miR‐21 in BMSCs‐derived exosomes inhibited PTEN, but enhanced AKT phosphorylation and Foxp3 expression in Tregs. In addition, EGF enhanced c‐jun phosphorylation to elevate the miR‐21 expression. Furthermore, EGF significantly increased the efficacy of BMSCs in a mouse model of aGVHD, manifesting in reduced IFN‐γ expression and lesser organ damage. Moreover, EGF treatment promoted the Foxp3 expression of Tregs in BMSCs‐treated aGVHD mice. Taken together, EGF induced the BMSCs‐derived exosomal miR‐21 expression, which enhanced Foxp3 expression in Tregs, thereby improving the therapeutic effect of BMSCs on aGVHD.